2002
DOI: 10.1002/pola.10253
|View full text |Cite
|
Sign up to set email alerts
|

Helical chirality of π‐conjugated main‐chain induced by polymerization of phenylacetylene with chiral bulky pinanyl groups: Effects of the flexible spacer and polymerization catalyst

Abstract: Three optically active phenylacetylene polymers with chiral bulky pinanyl groups, (Ϫ)-poly[4-(dimethylpinanylsilyl)phenylacetylene] [(Ϫ)-poly(PSPA)], (ϩ)-poly{4-[3-(10-pinanyl)tetramethyldisiloxy]phenylacethylene} [(ϩ)-poly(PDSPA)], and their copolymer [(Ϫ)-copoly(PSPA/PDSPA)], were synthesized. We observed high chirality in the main-chain chromophore of (Ϫ)-poly(PSPA), due to the presence of a chiral helix, with circular dichroism spectroscopy. In contrast, (ϩ)-poly(PDSPA),with flexible SiOSi spacers between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 21 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…Although many polymers having chiral structures in the main chain have been synthesized [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], there are only a few examples of chiral polymers whose chiral properties arose only from their chiral conformational structures, without the coexistence of any other chiral moieties such as a chiral end group from an initiator, or chiral pendant groups or asymmetric carbon from monomers [17][18][19][20]. Recently, the authors reported the first successful helix-sense-selective polymerization of a phenylacetylene (DHPA, Scheme 1) using a chiral catalytic system [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although many polymers having chiral structures in the main chain have been synthesized [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], there are only a few examples of chiral polymers whose chiral properties arose only from their chiral conformational structures, without the coexistence of any other chiral moieties such as a chiral end group from an initiator, or chiral pendant groups or asymmetric carbon from monomers [17][18][19][20]. Recently, the authors reported the first successful helix-sense-selective polymerization of a phenylacetylene (DHPA, Scheme 1) using a chiral catalytic system [22].…”
Section: Introductionmentioning
confidence: 99%
“…Stable optically active polymers with a helical structure have been synthesized by many approaches, including the introduction of an optically active substituent to the polymer side-chain, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] an optically active amine to a substituted polyacetylene, [15,16] or optically active camphor sulfonic acid to polyaniline in order to induce chiroptical properties. [17,18] Helical polyacetylene with very stable chiroptical properties has been synthesized in chiral nematic liquid crystals as a reaction field.…”
Section: Introductionmentioning
confidence: 99%
“…We synthesized new poly(phenylacetylene)s having oligopinanylsiloxanes as side groups ( Figure 5). [82][83][84] The polymers had self-membrane-forming abilities. Similarly to the results of poly(disubstituted acetylene)s in 3.7.3, as the content of the chiral groups increased, the enantioselectivities increased as shown in Figure 6.…”
Section: Macromolecular Design Of Polymericmentioning
confidence: 99%